BURNOUT SYNDROME: WORKER'S ILLNESS AND LEAVE OF JOB (CIPEEX, 2025)
This study aims to analyze Burnout Syndrome, a physical and emotional exhaustion related to the work environment and its consequences for the worker, especially in terms of absence from work. The research seeks to understand the factors that lead to the development of Burnout, its impacts on the worker's physical and mental health, and the measures adopted for its treatment and prevention. The research was carried out through a review of scientific literature on Burnout Syndrome, focusing on studies that investigate its causes, symptoms and the illness process in the workplace. Data from reports from health bodies, such as the World Health Organization (WHO), on the impact of the syndrome on productivity and worker absence were also analyzed. In addition, clinical cases and research related to the diagnosis, treatment and prevention of Burnout in different professional sectors were reviewed. The results indicate that Burnout Syndrome is more common in professions that require high levels of emotional interaction, such as teachers, healthcare professionals and administrative employees. The main symptoms include extreme exhaustion, lack of motivation, feelings of failure and depersonalization, which significantly affects professional performance. Research shows that, in many cases, Burnout leads to removal from employment, either through temporary medical leave or, in more serious situations, due to the permanent inability to return to work. Affected workers report difficulties in reconciling their personal and professional lives, as well as problems such as depression and anxiety. The lack of support in the work environment and the constant pressure for results were identified as critical factors that contribute to illness. Burnout Syndrome is a significant occupational health problem, which affects both the worker's quality of life and the efficiency of organizations. The study concludes that it is essential to implement stress prevention and management policies in the workplace to reduce the incidence of Burnout. This includes measures such as reducing workload, flexible working hours, promoting well-being activities and psychological support. Furthermore, it is necessary for employers to recognize the early signs of the syndrome and offer adequate support to employees to prevent the problem from evolving into more serious stages. Leave from work, when necessary, must be accompanied by a gradual reintegration plan, focusing on the worker's full recovery and readjustment of working conditions.
Keywords: burnout syndrome; mental illness; labor law; safe working environment